2022
DOI: 10.1002/kjm2.12566
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC01419 promotes hepatocellular carcinoma malignancy by mediating miR‐485‐5p/LSM4 axis

Abstract: To investigate the effect of long noncoding RNA (LINC01419)/miR‐485‐5p/LSM4 on the malignant behavior of hepatocellular carcinoma (HCC) cells. The expressions of LINC01419, miR‐485‐5p, and LSM4 were determined in HCC at the cellular and clinical levels, and cell biological behavior was evaluated. The relationships between LINC01419, miR‐485‐5p, and LSM4 were predicted and verified. Additionally, the subcellular localization of LINC01419 in HCC cells was analyzed. Finally, an animal experiment was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…High LSM4 expression enhanced ovarian cancer cell proliferation, metastasis and glycolysis 28 . LSM4 had increased expression in hepatocellular carcinoma and could serve as a diagnostic marker, which upregulation contributed to cell malignant behaviors 29,30 . Although LSM4 has been shown to be oncogenic in many cancers, its role in NSCLC progression has not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High LSM4 expression enhanced ovarian cancer cell proliferation, metastasis and glycolysis 28 . LSM4 had increased expression in hepatocellular carcinoma and could serve as a diagnostic marker, which upregulation contributed to cell malignant behaviors 29,30 . Although LSM4 has been shown to be oncogenic in many cancers, its role in NSCLC progression has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“… 28 LSM4 had increased expression in hepatocellular carcinoma and could serve as a diagnostic marker, which upregulation contributed to cell malignant behaviors. 29 , 30 Although LSM4 has been shown to be oncogenic in many cancers, its role in NSCLC progression has not been explored. Database analysis revealed that LSM4 expression was high in LUAD tissues and could be decreased by SF3B4 knockdown in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…LSM4 has also been found to be upregulated in several types of cancer, such as breast cancer, and in early-stage pancreatic ductal adenocarcinoma, where it is associated with a poor prognosis [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%